Reporting inconsistency between published conference abstracts and article abstracts of randomised controlled trials in prosthodontics presented at IADR general sessions - Wang,Guanru; Chen,Junsheng; Li,Honglin; Miao,Cheng; Cao,Yubin; Li,Chunjie (PeerJ, 2023)
Background There is commonly a discrepancy between conference abstracts and published article abstracts in prosthodontic randomized controlled trials (RCTs), which may mislead the scholars those attend conferences. Objective To identify the characteristics predicting inconsistency between conference abstracts and published article abstracts in prosthodontic RCTs. Methods The conference abstracts of prosthodontic RCTs presented at the IADR general sessions from 2002 to 2015 were searched. Electronic searches of MEDLINE, EMBASE, the Cochrane Library, and Google Scholar databases were conducted to match full-text publications for conference abstracts. Two investigators extracted basic characteristics and assessed the consistency and reporting quality independently and in duplicate. The linear regression model was used to analyze the predictors of inconsistency. Results A total of 147 conference abstracts were matched with published articles. Results for the secondary outcome measure, Statistical analysis, and precision measure were less than 50% consistent, and even nearly 5% of the studies had opposite conclusions. Multiple linear regression analysis showed that three factors were correlated with lower inconsistency, including continent of origin (p = 0.011), presentation type (p = 0.017), and difference in reporting quality (p = 0.013). Conclusion Conference attendees should cautiously treat the findings of the conference abstracts. Researchers should improve the precision of the information delivered at conferences. We recommend the authors of RCTs to explain the primary difference between conference abstracts and article abstracts.
Keywords: Prosthodontics; Conference abstracts; Inconsistency; Discrepancy; Congresses as topic